MEMBANGUN UMKM DAN KEGIATAN KEAGAMAAN UNTUK ANAK-ANAK DAN REMAJA DI DUSUN VIII DESA KOTA DATAR KECAMATAN HAMPARAN PERAK KABUPATEN DELI SERDANG PROVINSI SUMATERA UTARA. - Siti Suharni Simamora, Irhamuddin, Yuni Asri Ningratri, Indah Fitria Rahmah, M Baihaqi (JURNAL BIMA, 2025)
Implementation of Real Work Lectures (KKN) at the Tarbiyah Al-Washlyah Binjai College of Science is a concrete manifestation of the Tri Dharma of Higher Education. Student KKN activities aim to develop student competencies and demonstrate the knowledge and skills they possess so that they are able to design and implement programs that can realize village development based on their scientific fields. It is hoped that the community will be able to provide motivation, innovation and create creativity in the development of knowledge so that students are able to become facilitators in the development and application of knowledge and technology.